Reliability and validity of a post-traumatic checklist-5 (PCL-5) among fire and rescue officers in Selangor, Malaysia - Muhammad Naim Mat Salleh; Halim Ismail; Hanizah Mohd Yusoff (Journal of Health Research, 2021)
Purpose – This study is to establish the validity and reliability of Malay version of Post-traumatic Check List-5 (MPCL-5) among the fire and rescue officers in the state of Selangor, Malaysia. Design/methodology/approach – A cross-sectional study was conducted, which involved 100 firefighters from the state of Selangor, Malaysia. Construct validity, internal consistency, and concurrent validity were performed and analyzed using Statistical Package for Social Sciences (SPSS) version 20. Concurrent validity was tested with validated Malay version of Trauma Screen Questionnaire (TSQ-M). Findings – Overall internal consistency reliability was a 0.960 and individual construct Cronbach's alpha ranged from 0.827 to 0.926. The model, which consists of four constructs with 20 items, demonstrated the presence of acceptable loading factors. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) are 0.81, 0.65, 0.31 and 0.95 respectively at an optimum cut-off score of 35. Research limitations/implications – The Post Traumatic Check List 5 (PCL-5) is the latest tool based on DSM-5 developed recently and still having limited studies on the psychometric properties of the tool in local population and the findings produced are comparable with the results from validation from previous studies. The study limitations are population samples used are considering the minimum numbers of sample for each item for factor analysis and the concurrent validation was tested with the TSQ-M instead of the Clinician Administered PTSD Scale for DSM-5 (CAPS-5). Practical implications – The study suggested that MPCL-5 is acceptable to be used to measure post-traumatic stress disorder in local populations. Originality/value – There are limited known validation studies for PCL-5 in local populations and this is the first study done among fire and rescue officers in Malaysia. The results are comparable with findings from previous studies and therefore MPCL-5 are valid and reliable for PTSD screening.